Probabilistic characteristics of the aircraft deviation from the desired flight levels - Харченко, В.П.; Остроумов, І.В. (Proceedings of National Aviation University (archive), 2008)
The probabilistic characteristics of the aircraft deviation from the flight-planned level have been estimated. Deviation probability density has been used. Special program software has been used for estimation deviation probability density.